2003
DOI: 10.1002/prot.10468
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the α‐helix to β‐hairpin transition

Abstract: The aggregation of alpha-helix-rich proteins into beta-sheet-rich amyloid fibrils is associated with fatal diseases, such as Alzheimer's disease and prion disease. During an aggregation process, protein secondary structure elements-alpha-helices-undergo conformational changes to beta-sheets. The fact that proteins with different sequences and structures undergo a similar transition on aggregation suggests that the sequence nonspecific hydrogen bond interaction among protein backbones is an important factor. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
295
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 265 publications
(310 citation statements)
references
References 53 publications
13
295
0
2
Order By: Relevance
“…Our results show that both a repulsive db and a physically realistic range of cm attraction of ∼5.0Å between methyl or methylene groups tend to favor β over α structures, at least for the polyalanine, polyvaline, and polyleucine chains we have studied. This finding may help to assess prior studies that used effective ranges of cm attraction as large as 6.5Å [31,32]. db's arise from empty spaces created by water exclusion between hydrophobic groups [37][38][39][40]42] and are the hallmark of interactions between nonpolar groups [33,34,[36][37][38][39][40][41][42][43] that are partially exposed to water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show that both a repulsive db and a physically realistic range of cm attraction of ∼5.0Å between methyl or methylene groups tend to favor β over α structures, at least for the polyalanine, polyvaline, and polyleucine chains we have studied. This finding may help to assess prior studies that used effective ranges of cm attraction as large as 6.5Å [31,32]. db's arise from empty spaces created by water exclusion between hydrophobic groups [37][38][39][40]42] and are the hallmark of interactions between nonpolar groups [33,34,[36][37][38][39][40][41][42][43] that are partially exposed to water.…”
Section: Discussionmentioning
confidence: 99%
“…An early simulation of a 12mer polyalanine indicated that its ground state was an α helix in vacuum and a β hairpin in aqueous solution [30]. However, subsequent simulations of aqueous short hydrophobic-polar [31] and polyalanine [32] peptides using different potential functions predicted an α-helical ground state except for very high hydrophobic interaction strengths [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed implementation of the covalent bonds and constraints that maintain the correct geometry of each residue and the peptide connectivity is described by Ding et al 34 Clustering Methods. Clustering is the procedure that categorizes or groups similar entities together on the basis of quantitative distance (similarity) measures.…”
Section: Dmd Simulation and Four-bead Protein Modelmentioning
confidence: 99%
“…We describe the use of simplified protein models in conjunction with the rapid simulations methodology, discrete molecular dynamics (DMD). Despite the use of DMD in simulating polymer fluids [6,7], single homopolymers [7,8], proteins [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], protein aggregates [13,17,23,24,26], and gases and liquids [27,28], we believe it is significantly underutilized in the molecular-modeling field.…”
Section: Introductionmentioning
confidence: 99%